Religion, Spirituality and Addiction Recovery: Introduction - Dossett, Wendy (Implicit religion, 2019)
Religion, spirituality, non-religion, and the secular (Lee 2014, 2015) are unstable categories that are nonetheless routinely reified by academics, clinicians and practitioners alike, and positioned as fundamental to experiences of addiction recovery. For instance, addiction is often framed, dramatically, as a spiritual malady, yet, just as often, as simply a poor moral choice. While ideas associated with religion or spirituality play out differently in those contrasting diagnoses, the role of religion and spirituality in their aetiology is evident. We (Wendy Dossett and Liam Metcalf-White) argue that the categories of religion, spirituality, and non-religion, as they to relate to addiction recovery, need further analysis than they receive in the clinical literature. This literature frequently presents them as extra "technologies of the self " (Foucault 1988); either functionally worthwhile or not (Szalavitz 2017); rather than as embedded in the very culture and discourses in which addiction and recovery are named and experienced. We argue for a focus on the latter as more productive for an understanding of the field.